Effects of maturity of Kamias (Averrhoa bilimbi) on the characterization of jelly. - Bugna, Neziah Raborar (2017.)
The utilization of green and ripe kamias for production of jelly was investigated based on physicochemical properties and sensorial attributes. The physicochemical properties tested were: pH, water activity (Aw), total soluble solids (TSS), titratable acidity in terms of oxalic acid (TA), and ascorbic acid content. Sensorial attributes assessed were: sweetness, sourness, kamias taste, firmness, and general acceptability. The green kamias jelly?s TA as oxalic acid was the only physicochemical attribute tested that was significantly different from ripe kamias jelly using Mann-Whitney test at 95% confidence level. Green kamias jelly had a mean pH of 3.19, water activity of 0.969, TSS of 32.93°Brix, TA of 0.41%, and ascorbic acid content of 1.64 mg/50 g. Ripe kamias jelly had a mean pH of 3.18, water activity of 0.964, TSS of 32.47°Brix, TA of 0.35%, and ascorbic acid content of 1.34 mg/50 g. The sensory evaluation showed the median score of green kamias jelly was sweet, moderately sour, moderate kamias taste, and firm while the median score of ripe jelly kamias jelly was moderately sweet, moderately sour, moderate kamias taste, and moderately firm. No significant differences were observed between green and ripe kamias jelly in their descriptive attributes using Mann-Whitney test at 95.0 confidence level. The green and ripe kamias jellies were generally accepted. However, the green kamias jelly was scored higher in acceptability than the ripe kamias jelly. Only the TA and the general acceptability were sigificantly affected by the maturity level of kamias as green and ripe.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Kamias; Averrhoa bilimbi; Jelly